An Exploratory Study: Mothers’ Perceptions of the Determinants of Stunting Among Toddlers in the Working Area of UPTD H.A.H Hasan Public Health Center, Binjai - Randy Frananta Ginting; Ermi Girsang; Sri Lestari Nasution (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction:Stunting remains a major public health issue in Indonesia, including in the working area of UPTD Puskesmas H.A.H Hasan Binjai. Mothers’ perceptions and feeding practices are critical determinants influencing child growth and nutritional status. Understanding how mothers perceive the direct and indirect causes of stunting is essential to develop effective, culturally appropriate interventions at the community level. Methods:This study employed a qualitative exploratory design to explore mothers’ perceptions of stunting determinants. In-depth interviews were conducted with eight informants, comprising five mothers of toddlers, one community health volunteer, one village midwife, and one nutrition officer. Data were analyzed thematically through data reduction, data display, and conclusion drawing following the Miles and Huberman framework. Results:The findings indicated that most mothers had limited understanding of nutrition, emphasizing food quantity rather than quality. Exclusive breastfeeding practices were suboptimal due to misconceptions that watery breast milk lacks nutrition. Complementary feeding (MP-ASI) was monotonous and low in animal protein. Indirect determinants such as unstructured parenting, limited family support, and poor economic conditions contributed to stunting risk. The main barriers identified were economic hardship, time limitations, and limited access to health services. Mothers with positive perceptions demonstrated more consistent preventive behaviors, such as exclusive breastfeeding, providing diverse complementary foods, and active participation in community health programs. Conclusions:Mothers’ perceptions significantly influence stunting prevention behaviors. Low nutritional literacy, cultural beliefs, and economic challenges remain key barriers. Effective prevention efforts require family-based and culturally tailored nutrition education supported by community health cadres to enhance maternal understanding and sustainable child health practices. Keywords:Mothers’ perception, stunting, prevention